The Effects of Energy Consumption, Economic Growth, and Financial Development on CO2 Emissions in Greece - Muhammad Atif (Arthatama, 2021)
This study aims to assess the effects of energy consumption, economic growth, and financial development on co2 emissions in Greece. This study has adopted a quantitative design where data has been gathered from World Bank and Greek Government’s website from 1990 to 2018. The variables include renewable and fossil fuel energy consumption, domestic credit to the private sector, GDP growth rate and CO2 emission in metric tons. Data is analysed using ADF, VECM and Granger Causality tests applied through STATA. The results have revealed a long-run relationship effect of financial development on CO2 emissions in Greece, whereas a short-run effect of economic growth on CO2 emissions is also determined. The results are applicable to Greece only since the data was taken specifically from Greece